PENGARUH PENGGUNAAN VARIASI PUPUK PADA PERTUMBUHAN PADI SEBAGAI PETUNJUK PRAKTIKUM MATERI PERTUMBUHAN DAN PERKEMBANGAN PADA TANAMAN - nuriwardani (Universitas Muhammadiyah Metro, 2025)
Rice is a rice-producing plant which is a staple food source for half of the world's population. To continue to increase and stabilize rice production, fertilizer is of course needed as a source of nutrition for plants. Synthetic chemical fertilizer is a type of fertilizer commonly used by farmers. However, excessive use of synthetic fertilizers has a negative impact on the ecosystem. This research was conducted using a Completely Randomized Randang (CRD) design with 6 treatments and 10 repetitions. Data collection was carried out through observation techniques and data analysis using the One Way Anova test and Tukey's advanced test with a significance level of 5%. P5 treatment with a combination of 70% pumakkal fertilizer and compost with 30% synthetic fertilizer showed the best results with plant height reaching 104.5 cm, number of stems in each clump of 42 stems, productive clumps of 24 stems, production yield of 2, 95g on each stem with a total of 242 grains. The research product in the form of practical instructions which have been validated by design experts obtained a percentage score of 86.5% in the very good category and the results of validation by material experts also showed the same thing, getting a percentage score of 81.25% with very good criteria and suitable for use in practical activities at school.